2015
DOI: 10.1111/anu.12400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fibre Concentrates on growth performance and digestive enzyme activities of jundiá (Rhamdia quelen)

Abstract: This study was conducted to investigate the prebiotic effect of different Dietary Fibre Concentrates (DFC) (Mucilage = MG; Pectin = PN or b-glucan + mannan = bg + M) on growth and somatic parameters, body composition and digestive enzyme activities of jundi a (Rhamdia quelen). After acclimation, fish (7.16 AE 0.06 g) were allocated into 24 tanks (30 fish per tank) and triplicate groups were fed with Control diet (0 g kg À1 of DFC); diet supplemented with 5 g kg À1 commercial prebiotic (CP) or diets supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
6
12
0
1
Order By: Relevance
“…They also reflected in growth promoter effect (diets 1:2 and 1:4), increasing the final fish weight, without affecting the apparent feed conversion. Similar results were reported for silver catfish (Goulart et al, ) and Oreochromis niloticus (Mombach, ) when evaluating the administration of prebiotic doses of linseed soluble fibre (mucilage) in diets. Demonstrating that the formulation of diets can be manipulated to balance the amount of dietary fibre in order to obtain positive results from its presence.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…They also reflected in growth promoter effect (diets 1:2 and 1:4), increasing the final fish weight, without affecting the apparent feed conversion. Similar results were reported for silver catfish (Goulart et al, ) and Oreochromis niloticus (Mombach, ) when evaluating the administration of prebiotic doses of linseed soluble fibre (mucilage) in diets. Demonstrating that the formulation of diets can be manipulated to balance the amount of dietary fibre in order to obtain positive results from its presence.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies conducted by our research group have shown that the sources and solubility of fibres cause different effects on animal metabolism and growth (Adorian et al, , ; Goulart et al, ). Among the researched fibre sources, linseed fibre has demonstrated excellent prebiotic functionality (Adorian et al, , ).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The final weight and condition factors of the jundiás increased in response to the increase in the level of rice bran protein concentrate. This difference observed between treatments with RBPC may be related to the higher levels of neutral detergent fibre found in the RBPC20 and RBPC30 diets because the fibre that is not digested becomes available for fermentation by the microflora in the posterior gut of the fish, thereby providing a possible prebiotic effect (Goulart et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Adorian et al (2015) questionaram o efeito da fi bra alimentar em dietas para peixes, constatando que essa fração pode melhorar o desempenho animal, atuando como promotor de crescimento. Da mesma forma, Goulart et al (2015) demonstraram que diferentes concentrados de fi bra alimentar suplementados a dietas de jundiás (Rhamdia quelen) proporcionam efeito semelhante ao proporcionado pela utilização de prebióticos comerciais.…”
Section: Efeito Prebiótico Da Fibra Alimentarunclassified